Capturing Peer-To-Peer Mentoring Advice : A Podcast Series for First-Year Law Students. - Mackay, Anita (Student Success v.15 n.1 p.114-121 https://doi.org/10.5204/ssj.2992, 2024)
This practice report provides an overview of a podcast series designed to support first-year student transition to university and promote wellbeing and belonging. The podcast was established in 2017 in a compulsory first year law subject (Legal Institutions and Methods) at La Trobe University, Australia. The podcasts record interviews with students who have recently completed the subject and are designed to (a) give interviewees an opportunity to reflect on their experiences and (b) provide advice to future commencing law students (i.e., their peers). The podcast is a form of peer-to-peer mentoring that requires a relatively small investment of resources and provides on-demand support to students as they commence their law studies. The concept is readily adaptable to other disciplines. [Author abstract]